2006
DOI: 10.1109/dft.2006.62
|View full text |Cite
|
Sign up to set email alerts
|

Test Generation for Open Defects in CMOS Circuits

Abstract: Open defects in CMOS circuits require two-pattern tests for detection. Traditionally, the only two-pattern tests included in manufacturing test are those targeting transition delay faults. Such tests, however, do not provide complete coverage of all the open defects. In this paper we propose the use of a unified test set that detects all inline resistance faults which model interconnect open defects and all transistor stuck-open faults which model intra-gate open defects in order to obtain a comprehensive cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As we describe below, there is a second mechanism that can generate open fault activating hazards -these are focus of this work. The failure of LOC TDF tests to detect some potentially easily detectable transistor stuck-open defects was addressed in [6] by modifying the LOC TDF test generation requirements to additionally force a transition at the gate output when targeting TDFs at the transistor inputs. However, there were still a significant number of opens that remained undetected by this explicit procedure to target TSOFs, i.e.…”
Section: Background and Prior Workmentioning
confidence: 99%
“…As we describe below, there is a second mechanism that can generate open fault activating hazards -these are focus of this work. The failure of LOC TDF tests to detect some potentially easily detectable transistor stuck-open defects was addressed in [6] by modifying the LOC TDF test generation requirements to additionally force a transition at the gate output when targeting TDFs at the transistor inputs. However, there were still a significant number of opens that remained undetected by this explicit procedure to target TSOFs, i.e.…”
Section: Background and Prior Workmentioning
confidence: 99%
“…A recent industrial study [1] There has been research on testing open defects reported in the literature going back many decades. Some more recent papers [3,4] have been proposed enhancing the open defect coverage of TDF test to also target the transistor stuck-open faults (TSOFs) by adding the constraint to the ATPG to additionally require gate output initialization when targeting TDFs at gate input nodes. However, the open fault coverage improvement from this approach appears limited, as a large number of TSOFs remain undetectable.…”
Section: Introductionmentioning
confidence: 99%
“…Hillebrecht et al [8] developed a flow that integrates the physical information (including the layout and the cell library) and the aggressor -victim model for pattern generation. Devtaprasanna et al [9] gave a solution of testing intra-gate open defects and obtained the complete defect coverage. Gomez et al [10] used the commercial tool to build a flow from layout extraction to Automatic Test Pattern Generation (ATPG) for interconnect open defect.…”
Section: Introductionmentioning
confidence: 99%